Screening Microbial Contamination of Smoking Waterpipe (Narghile) in Erbil city/ Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Tobacco smoking, which is a traditional habit is a major health risk worldwide. However waterpipe (Narghile) smoking is an emerging smoking type, specifically among Erbil/ Iraq. In the recent years, smoking of Shisha (Narghile) has spread amongst adolescents and young adults in Erbil city. The aims of this study are to examine the prevalence of shisha pipe smoking in Erbil city and to determine the microbial pathogen contaminants present in these Shisha pipes. In this study, we performed a qualitative and quantitative analysis of the microbial contamination of (90) Shisha hose samples in Erbil. Eighteen samples were selected from each cafe and swabs were cultured and identified. Results showed that most Narghile users 82.2 % were male and half of them (50%) were in the age group of 20-30 years followed by the age group of 30-40 years. Data showed that 54% of the samples were contaminated, from them most microbial pathogens were G+ve bacteria. Staphylococcus albus and Staphylococcus aureus were among the most isolated pathogens, however E. coli was the most common G-ve bacteria in this study. On the other hand the number of fungi and yeasts identified in this study were 7 isolates, among them Monilia, Paecillomycet spp and Aspergillus niger were most common isolates. In conclusion, data produced from this study showed that Narghile users are exposed to many infectious microbial agents, because many users are unaware of the associated microbial contaminations and smoke narghile as a safe alternative to cigarette smoking. More research, should focus on strategies on how to avoid shisha smoking as the impact of its use is expected to affect the health and life of many people in our local community.